Endothelial RNF20 suppresses endothelial-to-mesenchymal transition and safeguards physiological angiocrine signaling to prevent congenital heart disease - Dou, Yanliang; Tetik-Elsherbiny, Nalan; Gao, Rui; Ren, Yonggang; Chen, Yu-wen; Merbecks, Moritz B.; Setya, Aadhyaa; Lityagina, Olga; Wang, Yinuo; Chichelnitskiy, Evgeny; Abouissa, Aya; Wu, Chi-Chung; et al. (Nature Communications, 2025)
Heart morphogenesis and function rely on intricate communication among distinct cardiac cell types. How their co-development and crosstalk are coordinated is largely unexplored. Our study unveils key functions of the histone H2B ubiquitin (H2Bub1) ligase RNF20 in second heart field development and cardiac endothelial cells. We demonstrate that RNF20 promotes Nrg1 expression through a RNF20-H2Bub1-dependent mechanism and restrains TGF-β signaling by influencing RNA polymerase II pause release at TGF-β target genes in endothelial cells. While heightened TGF-β signaling following RNF20 loss results endothelial-to-mesenchymal transition (EndMT), both impaired Nrg1 signaling and elevated TGF-β activity contribute to abnormal cardiomyocyte proliferation and contractility. Importantly, RNF20 expression is significantly reduced in cardiac endothelial cells from congenital heart disease patients showing a positive correlation with oxygen saturation and a negative correlation with key components and downstream effectors of TGF-β signaling. In summary, our work identifies a crucial role for RNF20 in safeguarding endothelial identity and physiological angiocrine signaling, thereby ensuring proper heart development and function.
Online veröffentlicht: 27. Oktober 2025
Gesehen am 09.12.2025